A numerical investigation of heat transfer process in paraffin/ethylene-vinyl acetate/graphene aerogel ternary composite. (25th May 2021) - Liu, Xu; Yang, Wenbin; Feng, Zhicheng; Li, Yongsheng; He, Fangfang; Fan, Jinghui; Wang, Renchao; Zhang, Kai; Yan, Hongjian
Highlights: The heat transfer process of Pa/EVA/GA were predicted by VAM. The two-temperature model was adopted. GA significantly improved heat transfer performance of Pa. EVA increased the viscosity of paraffin and accelerated heat transfer. Abstract: Melting and solidification heat transfer characteristics of different paraffin/ethylene-vinyl acetate/graphene aerogel (Pa/EVA/GA) composites were predicted by the volume-averaged method (VAM). In parameter settings, Pa/EVA was treated as fluid, and GA was set to solid. The two-temperature model based on the assumption of local thermal nonequilibrium was adopted to solve the large difference in thermal conductivity between GA and Pa/EVA. The simulation results were validated by experimental data. The numerical results denoted that GA and EVA significantly improved heat transfer performance of Pa and reduced the melting/solidification time. The heat transfer of the composites was dominated by heat conduction, as the three-dimensional skeleton of GA and the high viscosity of EVA inhibited the natural convection of paraffin. Compared with Pa/EVA0 /GA, Pa/EVA5 /GA and Pa/EVA10 /GA had a higher surface heat flux, decreased the velocity of paraffin, and had a more even temperature distribution.